An analysis of Covid-19 implications for SMEs in Pakistan. Issue 1 (3rd February 2021) - Aftab, Rehan; Naveed, Muhammad; Hanif, Sajjad
Abstract : Purpose: The purpose of this paper is to ascertain the impact of coronavirus (Covid-19) on small and medium enterprises in Pakistan, which are vulnerable to crisis situations. This study also aims to provide policy recommendations to the stakeholders by reviewing the situation of small and medium scale enterprises (SMEs) after the Covid-19 sudden surge. Design/methodology/approach: The descriptive study is based on quantitative data technique and primary data collection is undertaken. The survey instrument is adapted from the US Bureau of Labor Statistics public documents. Collected responses from SME owners are descriptively analyzed using appropriate graphs. Findings: The analysis infers that SMEs in Pakistan have encountered unfavorable implications of Covid-19 in the form of shortage of goods, blockage in transportation, decrease in demand of products and services, decline in profits and sales, limited operations, lockdown and employee's layoff. Research limitations/implications: The limited sample and precise use of instruments are few limitations along with valuable implications of this research. The analysis of Covid-19 impact on SMEs is an ongoing phenomenon and aids in proactive planning for the second wave of this outbreak. Financing schemes, youth entrepreneurship loans, retention of skilled staff and proactive planning for adverse future are few recommended measures for revival of the SMEs sector. Originality/value: The use of a unique sample and quality data set collected using the Bureau of Labor Statistics instrument adds value to the findings of the study and their consistency. The existing body of knowledge in the context of the SMEs sector of Pakistan is strengthened with an analysis of crisis implications for this sector, which remained unaddressed in the past.